Evaluation of Survival Time of Tooth Color Dental Materials in Primary Anterior Teeth - Taraneh Movahhed; Abbas Makarem; Masoumeh Ebrahimi; Behjat-; Amir Reza Motamedi (Mashhad University of Medical Sciences, 2012)
Introduction: In restorative dentistry, selecting the proper material is an important factor for clinical success. The objective of this study was clinical evaluation of survival time of three tooth color materials in primary anterior teeth. Methods: In this interventional clinical trial study, 94 deciduous anterior teeth (36 teeth in boys, 58 teeth in girls) belonging to 3-5 year old children in Pediatric Department of Mashhad Faculty of Dentistry, Iran were selected. Selective dental materials included compoglass, glass-ionomer Fuji II LC, and composite resin. The data were analyzed with Kaplan-Meyer and Log rank test. Results: compoglass had the highest survival time in comparison with composite and glass-ionomer. Nine months retention rate for teeth restored with compoglass, composite resin and glass-ionomer were estimated: 95%, 21%, and 12.5%, respectively. Conclusion: Compoglass can be a suitable material for anterior primary teeth restoration.